Ferromagnetism Induced by Magnetic Dilution in Van der Waals Material Metal Thiophosphates. Issue 3 (10th February 2023) - Peng, Jin; Yang, Xinyu; Lu, Ziye; Huang, Lin; Chen, Xiyu; He, Miao; Shen, Jingdong; Xing, Yu; Liu, Meifeng; Qu, Zhe; Wang, Zhicheng; Li, Linglong; et al.
Abstract: Metal thio(seleno) phosphates MPX3 attract considerable attention with potential application in spintronics and other types of devices. Here, ferromagnetism in an Ising type diluted magnetic semiconductor Fe1‐ x Zn x PS3 is reported. Bulk single crystals of Fe1‐ x Zn x PS3 have been synthesized via chemical vapor transport method and characterized by X‐ray diffraction. The weak ferromagnetism associated with spin/cluster spin glass emerges at 30% Zn doping. A nearly static ferromagnetic order is observed in the highly diluted magnets Fe0.1 Zn0.9 PS3 . X‐ray photoemission measurements indicate introduction of holes and associated Fe 3+ in samples with ferromagnetic order. Density functional theory calculations confirm the Ising‐type ferromagnetic state in highly diluted compounds with hole doping. The interplay between bound magnetic polarons induces impurity‐band‐exchange and superexchange interactions can explain the evolution of magnetism with Zn doping. The findings suggest that the magnetic diluted FePS3 system is a candidate for potential applications in magnetic devices, and its quantum mechanism should be explored by using microscopic techniques in the near future. Abstract : Ferromagnetic evidences have been observed in high‐diluted Fe doped non‐magnetic Van der Waals material ZnPS3 . Bound magnetic polarons induced by impurity are probably responsible for the establishment of long range Ising‐type ferromagnetic order, as partailly confirmed by density functional theory calculations.